Psychology of science implicit and explicit processes - Purdue Symposium on Psychological Sciences 2010 : Purdue University); Proctor, Robert W.; Capaldi, E. John. (New York ; Oxford : Oxford University Press, 2012)
This title brings together contributions from leaders in the emerging discipline of the psychology of science with other experts on the roles of implicit and explicit processes in thinking.
SYmposium held at Purdue University, June 4-5, 2010.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Reasoning -- Congresses; Science -- Philosophy; Science -- Psychological aspects -- Congresses